Influence of Digital Marketing on Customer Satisfaction Of Bank Jabar Banten Syariah (BJBS) and the Implications On Corporate Image - Lazuardi, Aldi Rahman; Raras TS, Anggono; Sudaryo, Yoyo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The development of technology in this digital era is growing so fast. Indirectly, the use of digital technology can be adapted to human needs and make things that are done manually turn into practical and more modern. Currently, many banking institutions have implemented digital marketing in marketing their products, including Islamic banking institutions such as Bank Jabar Banten Syariah (BJBS). This study aims to analyze the influence of using Digital Marketing on BJBS Customer Satisfaction and its implications for Corporate Image.Â  The method used in this study is a quantitative method with a verification approach. The instruments used are digital marketing variable questionnaires, customer satisfaction questionnaires and corporate image questionnaires. Interview techniques were used to explore aspects related to BJBS as well as documentation studies to complete this research. Data analysis technique using path analysis. The results of the study show that there is a positive influence between the use of Digital Marketing and BJBS Customer Satisfaction; there is a positive influence between BJBS Customer Satisfaction and Corporate Image; there is a positive influence between Digital Marketing and Corporate Image; and there is a positive influence between Digital Marketing on Company Image through BJBS Customer Satisfaction, or indirectly Digital Marketing influence BJBS Customer Satisfaction which has implications for Corporate Image